Inovasi Ekonomi Kreatif Mengatasi Sampah Plastik dengan Pemeriksaan Sistem Pengendalian Internal - Wibowo, Muhammad Eko Ari; Sriarwi, Sriarwi; Septanta, Rananda; Ramdani, Chaeru Syahru (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Plastic waste remains a critical environmental issue, particularly in urban and densely populated areas. This community service activity aimed to address the problem of plastic waste through an innovative approach that combines creative economic initiatives with the examination of internal control systems. The activity was conducted at the Dompet Yatim dan Dhuafa Pamulang Dormitory and involved 30 resident students as participants. Ten lecturers from Universitas Pamulang acted as facilitators. The program focused on empowering participants by introducing them to creative economic solutions that transform plastic waste into valuable products while ensuring accountability through internal control mechanisms. The implementation method included presentations of material, interactive discussions, and hands-on practice. As a result, participants gained an understanding of the economic potential of plastic waste recycling and the importance of internal control systems in managing such initiatives effectively. The activity not only enhanced the participants’ environmental awareness but also provided them with practical skills that could be used to support sustainable community-based entrepreneurship. This program contributes to the broader goal of fostering economic independence and environmental responsibility among youth.